A tale of false origins: Hyphessobrycon scholzei Ahl, 1937 and its junior synonym, Hyphessobrycon fernandezi Fernández-Yépez, 1972 (Teleostei: Characifomes: Acestrorhamphidae) - Lima, Flávio C.t.; Rodríguez-Olarte, Douglas; García-Alzate, Carlos A. (Zootaxa, 2025)
Hyphessobrycon scholzei Ahl, the black line tetra, or “Schwarzbandsalmler”, is a well-known tetra in the aquarium hobby, said to be originated from the lower Amazon basin in Pará state, Brazil. The species was for decades common in the aquarium hobby due to the easiness in its maintenance and breeding but reports of wild specimens were few and dubious. Hyphessobrycon fernandezi Fernández-Yépez was described from the río Yaracuy, an independent coastal drainage in northern Venezuela, and is only known from this and some adjacent small coastal river drainages, and the río Portuguesa drainage, río Orinoco basin. Based on morphological data, we herein argue that H. fernandezi is a junior synonym of H. scholzei. Circumstantial evidence herein assembled supports the idea that the purported type locality of H. scholzei is incorrect and that its type material, as well as the original stock that originated the aquarium population of the species, was very likely collected at the same occasion as the first specimens of Moenkhausia pittieri introduced in the aquarium hobby. We also discuss the conservation status of the species as well as its apparent demise from the aquarium hobby.